A cleavable self-aggregating tag scheme for the expression and purification of disulfide bonded proteins and peptides. (23rd November 2022) - Lin, Zhanglin; Jing, Yanyun; Huang, Yuan; Yang, Sha; Chen, Shuyi; Ou, Yingying; Pistolozzi, Marco; Yang, Xiaofeng
Graphical abstract: Highlights: Cleavable self-aggregating tag (cSAT) facilitates the correct folding of proteins. The yields of the six disulfide bonded proteins and peptides were 3–89 mg/L. 2.6 g/L of active human growth hormone was yielded by using cSAT in a 30-L scale. cSAT enables simple and fast removal of most of the host cell proteins. A standardizable method for protein production with markedly reduced time and cost. Abstract: The production of correctly folded, disulfide bonded proteins in high yields remains a technological challenge, especially for the commonly used expression system Escherichia coli . This work provides a standardizable method based on cleavable self-aggregating tag (cSAT) scheme that enables the facile production of a series of traditionally challenging disulfide bonded proteins and peptides. The yields of the six targets were in the range of 3 to 89 mg/L at the shake flask scale. Further scale up of human growth hormone resulted in a yield of 2.6 g/L in a 30-L fermenter. This cSAT scheme allows the correct folding of proteins and peptides in an aggregated form during expression, and can be combined to a standard two-step column purification to achieve high purity and high activity products. This promises a generally applicable platform for the production and purification of proteins and peptides with markedly reduced development time and cost.